2012
DOI: 10.2310/jim.0b013e318249fc95
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiogram Done Early in Neonatal Sepsis: What Does it Add?

Abstract: Neonatal sepsis is associated with LV diastolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
6
6
0
Order By: Relevance
“…A study conducted by Abtahi and Jafari [3] found that right ventricular and left ventricular Tei indexes were significantly higher in septic neonates as compared to non-septic neonates. Tomerak et al [15] stated significant difference in left ventricular diastolic dysfunction (lower E/A ratio in the septic than the non-septic newborns), while no difference was noticed in the LV systolic function (EF and FS) between septic and non-septic neonates. Abdel-Hady et al [16] stated that the TDI (Tissue Doppler Imaging) indexes of global myocardial function (RV and LV Tei indexes) were significantly higher.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Abtahi and Jafari [3] found that right ventricular and left ventricular Tei indexes were significantly higher in septic neonates as compared to non-septic neonates. Tomerak et al [15] stated significant difference in left ventricular diastolic dysfunction (lower E/A ratio in the septic than the non-septic newborns), while no difference was noticed in the LV systolic function (EF and FS) between septic and non-septic neonates. Abdel-Hady et al [16] stated that the TDI (Tissue Doppler Imaging) indexes of global myocardial function (RV and LV Tei indexes) were significantly higher.…”
Section: Resultsmentioning
confidence: 99%
“…Neonatal sepsis may or may not be associated with left ventricular diastolic dysfunction; however, cardiac injury as manifested by elevated levels of cardiac troponin T may complicate the clinical picture. 492,493 Abnormal peripheral vasoregulation with or without myocardial dysfunction is the primary mechanism for the hypotension accompanying septic shock in the neonate. 494 Therefore, infected neonates may present with hypotension and adequate perfusion (warm shock) or inadequate perfusion (cold shock).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…15 Another study in preterm neonates also had similar results, with mean LV-MPI of 0.27 (SD 0.16). 1 Several studies on neonatal sepsis in different situations have used MPI and hs-cTnT to diagnose cardiovascular dysfunction. Due to the specificity of cTnT to myocardial tissue and its high sensitivity for myocardial injury, hs-cTnT may be used as a biological marker for myocardial injury.…”
Section: Discussionmentioning
confidence: 99%